2020
DOI: 10.1016/j.heliyon.2020.e04380
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of pharmacy awareness campaigns conducted in selected high schools across Lagos, Nigeria

Abstract: Background: It is revealing that pharmacy as a key health care profession is almost invisible within more recent health policy initiatives in Nigeria. This research is an effort to improve awareness about the pharmacy profession. The target shall be young, science inclined individuals in high schools; they are the future. Objective: To assess the levels of knowledge of high school science students about pharmacy and their interest in becoming pharmacists before and after sessions of awareness and education abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…This study's results also revealed that most students had inadequate knowledge of pharmacy practice areas, consistent with previous findings from Lagos (Ghazali et al, 2020). A possible explanation could be the considerable number of students who intend to choose medicine as their preferred choice, the relatively lower number of practising pharmacists in northern Nigeria (Ekpenyong et al, 2018), and the low number of pharmacists compared to other health professionals.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study's results also revealed that most students had inadequate knowledge of pharmacy practice areas, consistent with previous findings from Lagos (Ghazali et al, 2020). A possible explanation could be the considerable number of students who intend to choose medicine as their preferred choice, the relatively lower number of practising pharmacists in northern Nigeria (Ekpenyong et al, 2018), and the low number of pharmacists compared to other health professionals.…”
Section: Discussionsupporting
confidence: 88%
“…The proportion of students interested in studying pharmacy was significantly higher than what was reported among secondary school students in Lagos (Ghazali et al, 2020). This result could be due to differences in the level of awareness of careers in pharmacy and the demographic characteristics of the various respondents.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations